HEALTHY PEDIATRIC ATHLETES HAVE SIGNIFICANT BASELINE LIMB ASYMMETRIES ON COMMON RETURN TO SPORT PERFORMANCE TESTS. Issue 3 (31st March 2019) - Magill, John; Myers, Heather; Esposito, Valentine; Messer, Michael; Lentz, Trevor; Riboh, Jonathan
Purpose/Hypothesis: Return to sport (RTS) after anterior cruciate ligament (ACL) reconstruction in children is associated with a much higher risk (˜30%) of subsequent ACL injury than in adults. Most RTS testing protocols use Limb Symmetry Indices (LSI) on physical performance tests (PPTs). This assumes that both lower extremities should be equal. We hypothesized that in the pediatric population, baseline limb asymmetry exists, limiting the clinical utility of LSIs. Since LSI > 90% is often used as a clinical cutoff for RTS, we defined a test as valid if 80% of healthy volunteers had an LSI > 90%. Number of Subjects: 63 Materials/Methods: This study included healthy volunteers ages 6-18 [mean age = 10.7 +/- 3.2 years; 34 females (54%)]. Pubertal Maturity Observation Scores (PMOS), sex, age, height, weight, and body mass index (BMI) were collected. Subjects performed ten PPTs: lower quarter Y-balance, stork balance, stork balance on BOSU, single leg squat (SLS), SLS on BOSU, clockwise and counterclockwise quadrant single leg hop (SLH), forward SLH, timed SLH, and triple crossover SLH. Subjects performed the items in the same order, but were randomly assigned the starting test and the starting limb. We developed a composite score for each limb by averaging trials, then calculated the absolute value of the side-to-side difference, and normalized this difference to the test mean to obtain a percentage side-to-side difference (%STS). Multivariable linear regression analysis was performed to assess the effect of age on limb symmetry while correcting for BMI, PMOS and sex. Results: %STS were not normally distributed for any PPT, therefore data were reported as medians and interquartile ranges. All PPTs showed baseline limb asymmetry, and none met our definition of validity. The most symmetric PPT was the clockwise quadrant hop test (%STS in females, median = 9.85, interquartile range = 4.63 – 18.7; %STS in males, median = 6.9, interquartile range = 3.64 – 14.04). The stork balance on BOSU test had the greatest limb asymmetry (%STS in females, median 41.4, interquartile range 10.1 – 71.3; %STS in males, median 47.6, interquartile range 18.2 – 66.7). PMOS was strongly correlated with age (Pearson's? = 0.83), and was excluded as a predictor variable. Age was an independent predictor of %STS only for the stork test (B = -1.15, 95% CI = -1.92 to -0.38, p = 0.004), with older subjects having less limb asymmetry. Conclusions: Healthy children have significant baseline limb asymmetries on PPTs that are commonly used for RTS decision making after ACL reconstruction. None of the PPTs evaluated in this study met our definition of clinical validity. Limb symmetry was typically not affected by subject age. Clinical Relevance: In light of these results, limb symmetry indices (LSI) should be utilized with caution in this population. Functional recovery may be better assessed by comparison to age and sex-specific norms. Figure 2. BOSU Stork Test Limb Symmetry